The Weight of Evidence From Electrophysiology, Observational, and Cardiovascular End Point Studies Demonstrates the Safety of Azithromycin. Issue 1 (21st September 2020) - Cook, Jack; Pressler, Milton L.; Damle, Bharat; Alemayehu, Demissie; Knirsch, Charles A.
Abstract : Increased use of azithromycin (AZ) in treating infections associated with coronavirus disease 2019 (COVID‐19) and reports of increased incidence of prolonged corrected QT (QTc) interval associated with AZ used with hydroxychloroquine prompted us to review the latest evidence in the literature, present additional analyses of human cardiovascular (CV) electrophysiology studies, and to describe sequential steps in research and development that were undertaken to characterize the benefit‐risk profile of AZ. Combined QTc findings from electrocardiograms taken during oral and i.v. pharmacokinetic‐pharmacodynamic studies of AZ suggest that clinically meaningful QTc prolongation is unlikely. Findings from several observational studies were heterogeneous and not as consistent as results from at least two large randomized controlled trials (RCTs). The QTc findings presented and observational data from studies with large numbers of events are not consistent with either a proarrhythmic action of AZ or an increase in frequency of CV deaths. Well‐powered RCTs do not suggest a presence of increased risk of CV or sudden cardiac death after short‐term or protracted periods of AZ usage, even in patients at higher risk from pre‐existing coronary disease.